Ethnographic Analysis of The Interrelationship Between Educational Policy, School Management and Development of Educational Quality in Rural Areas - Jasman Jasman; Ardhana Januar Mahardhani; Dewi Febriyanti; Haris Munandar; Sitti Rachmi Misbah (Journal on Education, 2024)
The purpose of this study is to analyze the impact of education policies in rural areas and the managerial quality of school management on improving the quality of education. This study uses a case study approach. Researchers collect data through interviews, observations and surveys. Changes in the education model in schools located in rural areas show a shift from conventional to participatory school management patterns. This change is driven by the democratization implemented by school management. Despite progress, schools in rural areas still face various challenges such as limited resources and accessibility. Gender inequality and prevailing norms that are very strong in rural areas often hinder efforts to create an inclusive environment. The results of the study indicate that school management initiatives are needed to provide better quality education for students in rural areas. Another conclusion of the study is that schools also have a role as a driver for the formation of character and student abilities that respect differences and increase student capacity.